Distribution of the dual in relation to sentential function of the noun and preservation of dual morphology in six Slovenian dialects: picture description task - Pavlič, Matic; Stepanov, Artur; Stateva, Penka (Slavia Centralis, 2023)
We conducted a psycholinguistic experiment on language production, namely a picture description task based on three keywords. We investigated the use of dual morphology on nouns and verbs in six Slovene dialects. As for the loss of the dual in these dialects, we compared our results with the typology of Slovene dialects presented in Jakop (2008), based on data from the Slovenian Linguistic Atlas. We could not relate the use of dual morphology to the number of preserved dual forms in a dialect, but only to the sentential function of the noun. The latter experimentally confirmed for the first time the previously suspected (Tesnière 1925) effect of verb agreement on the use of the dual in Slovenian.
Keywords: dual; noun; verb; agreement; Slovenian; psycholinguistics